Phenomena of Incest Abuse in Lampung - Marvenda, Laras; Zahwa, Tasya Mulisia; Hidayanti, Dewi Ayu; Suwandi, Gustya Disha (Jurnal Perempuan dan Anak, 2024)
Recently, people are often surprised by the many phenomena of sexual deviation committed by biological fathers or those who are still related by blood. Normally, the family is a place to complain and grow to be good and healthy children, but in fact there are families that damage the growth and development of children. The purpose of this research is to understand the factors that lead to incest sexual harassment and how to deal with incest. The method in this study is a qualitative research method with a library research approach. The results showed that the causes of sexual violence against children in the family were low education, the person's economic and formal education, environmental factors or place of residence, the influence of alcoholic beverages and a lack of understanding about religion and attitudes. victims Mitigation efforts are carried out through preventive and repressive efforts.